Assisted combustion synthesis and characterization of Pr0.6Sr0.4MnO3±δ nano crystalline powder as cathode material for IT-SOFC. Issue 1 (January 2017) - Matheswaran, P.; Rajasekhar, M.; Subramania, A.
Abstract: Pr0.6 Sr0.4 MnO3±δ (PSM) nano crystalline powders were synthesized as cathode material by assisted combustion method at intermediate temperature for 6 h using a novel aspartic acid as fuel. Thermal decomposition behaviour of the prepared nano powder was carried out by thermo gravimetric-differential thermal analysis. The crystallization behaviour and structural morphology of Pr0.6 Sr0.4 MnO3±δ nano powder was investigated by X-ray diffraction and SEM analysis. The average crystallite size was determined from X-ray line broadening analysis by using the Scherrer equation. This method remarkably reduced the synthesis time and temperature. The electrical conductivity of the sample was measured by the 'dc four probe' techniques in the temperature range of 500–800 °C.